The use of resorbable plate in complex pediatric parasymphysis fracture management: A rare case report - Andrianto Soeprapto; Fitriana; Vera Julia; Dwi Ariawan (Journal of Dentomaxillofacial Science, 2021)
Objective: The use of open reduction and internal fixation with resorbable plate is the best management for complex pediatric mandibular fractures as the potential growth and development of the mandibular. The most common resorbable plate in Indonesia is ®inion plate. Case Report: A 6 year old girl fell off her bicycle on a downhill road 30 minutes before the hospital admission. Comminuted basal triangle fracture of left mandibular parasymphysis from 3DCT imaging was found. Open reduction and internal fixation with resorbable plate and monocortical screws was performed from extraoral and intraoral approach. Conclusion: Management of complex pediatric parasymphysis fracture require ORIF with plating on inferior border of mandibular and using monocortical screws to avoid any damage to nearby tooth buds. The resorbable plates give good outcome and advantage in pediatric patients as their potential growth and development of the mandibular.